Pengaruh Latihan Loncat Naik Turun Bangku dan Jumping Jack di Lahan Rawa Terhadap Kemampuan Lompat Jauh Gaya Jongkok - Prayoga, Hegen Dadang; Maulana, Ahmad (Jurnal Porkes, 2022)
The purpose of this study was to determine the Exercise Jumping Up and Down Bench and Jumping Jack in Swamp Land Against Squat Style Long Jump Ability. For the male students of SMPN 1 Anjir, Kec. Anjir, Kab. Barito Kuala for the 2021/2022 academic year. This research is an experimental research with quantitative research type. The research population was the male students of Smpn 1 Anjir, while the sample of this research was 30 people who were determined using purposive sampling technique. Data collection techniques in this study are tests and measurements. Statistical data shows the value of determining the value of t table for db = 28 and = 0.05, namely t table = t (0.05;28) = 2.048. Thus, t0 = 73.851 > t table = 2.048 or H0 is rejected. Which means that if H0 is rejected, there is a difference in the population mean parameters between experiment I and experiment II. the calculation of the statistical percentage in the exercise method for the squat style long jump in the first experiment there was an increase of 5.7063% > compared to the second experiment which increased only 3.8531%. Which means that the jumping jack in the swamp in Experiment I is superior to going up and down the bench in Experiment II.